Strategy to Actualize Green Campuses Through Sustainable Transportation - Amin Pujiati; Prasetyo Ari Bowo; Reza Nadya Isabella Putri (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
The green campus program is an effort made by the Indonesian government to overcome environmental problems that occur due to pollution, one of which is the Surakarta City Government. By involving tertiary institutions, it is hoped that it will be able to become a concrete example of the realization of greening for the surrounding community to help create a green and environmentally friendly city. The high level of pollution that occurs is certainly accompanied by the high use of motorized vehicles. The purpose of this research is to determine the priority order of strategies that must be carried out to realize a green campus through sustainable transportation at Universitas Sebelas Maret. The method used in this research is descriptive qualitative. The data used are primary data. The analytical tool used is the Analytical Hierarchy Process (AHP) which is used to determine the priority order of strategies in realizing a green campus through sustainable transportation at Universitas Sebelas Maret. The results showed that the order of priority strategies in realizing a green campus through sustainable transportation is improving the quality of the environment, developing facilities and infrastructure and university policies. Based on these priorities, there must be collaboration that is also carried out by the academic community in order to realize this green campus. In addition, all strategic plans that have been prepared must be carried out accordingly.